Pengalaman mahasiswa melaksanakan model precede proceed dalam memberdayakan masyarakat tembalang - Hartati, Elis; Andriany, Megah (Jurnal Keperawatan Soedirman, 2012)
Empowerment is important in planning, deciding and managing resources in community to improve capacity and the economic, ecological, and social independence. Precede Proceed model used by nursing students in nursing process in Tembalang as pilot project areas. The aims of this study was identified empowerment process, individuals; family; groups with special need and community support to improve quality of life, benefits of empowerment, and obstacles that occur in empowering community. This study used four participants. The data analysis process based on Colaizzi’s. Application of empowerment has two themes: play group, and elderly pos yandu. Individuals, family, groups with special need and community supports to improve quality of life has three themes: goals, objectives, and who is involved. The benefits of empowerment has three themes: useful for students, community, and health center. The obstacles occured in empowerment community has two themes: resources in the community, and implementation of precede proceeds